ANALISIS EFEKTIVITAS PENGGUNAAN INFORMASI AKUNTANSI DI UMKM KABUPATEN BANYUMAS - Tjahjani Murdijaningsih; Sri Sundari (Majalah Imiah Manajemen & Bisnis, 2020)
This study is entitled "Analysis of the Effectiveness of Using Accounting Information in the SMEs of Banyumas Regency." This study aims to determine whether whether owner education, business scale, company age and accounting training have a significant effect on the use of accounting information at MSMEs in Banyumas Regency. The population in this study is the SMEs in Banyumas Regency. The sample is 35 SMEs in the city and outside the city. The results showed that of the four independent variables namely owner education, business scale, company age and accounting training had a significant effect on the use of information, this was required by the t value for all independent variables greater than t table and sig value smaller than 0.5 This shows that to increase the use of accounting information among MSMEs, they must pay attention to these four variables so that financial statements are expected to be well structured.